Pelatihan Pemanfaatan Teknologi Informasi Komunikasi Bagi Guru PAI di SD Negeri Sugiraya - Musi Banyuasin (International Forum of Researchers and Lecturers, 2023)
Today's technological developments require the world of education to immigrate by adjusting developments. Technology is an important part of the learning process, including for Islamic Religious Education teachers. This type of research is qualitative, with a descriptive approach. Data collection techniques through interviews, observation and documentation. The data analysis technique is by carrying out data reduction, presenting data and ending with data verification. The results obtained that training activities on the use of information communication technology for PAI teachers have been carried out at SD Negeri Sugiraya. This information and communication technology has become an important need in the PAI learning process. Teachers are given the opportunity to learn to develop information and communication technology skills that are beneficial in their learning process and in their daily lives as well as learning programs in educational institutions need to implement information system-based learning. Integrating information and communication technology into learning, among others, to improve teacher competence in teaching and improve the quality of learner learning. Innovative information and communication technology can improve what is being done now, as well as what we have not yet started using information and communication technology.